What Are the Applications of AI in Medical Research? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Artificial intelligence (AI) is no longer a concept confined to science fiction; it has become a transformative force in numerous fields, and medicine is no ...
Keywords: AI in Medical Education and Future of Healthcare; Applications; Medical; Research; Artificial Intelligence; Machine Learning; Deep Learning